2016
DOI: 10.1016/j.ajem.2016.06.051
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent violent injury: magnitude, risk factors, and opportunities for intervention from a statewide analysis

Abstract: Introduction Though preventing recurrent violent injury is an important component of a public health approach to interpersonal violence, and a common focus of violence intervention programs, the true incidence of recurrent violent injury is unknown. Prior studies have reported recurrence rates from 0.8% to 44%, and risk factors for recurrence are not well established. Methods We used a statewide, all-payer database to perform a retrospective cohort study of emergency department visits for injury due to inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
68
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(72 citation statements)
references
References 44 publications
(69 reference statements)
4
68
0
Order By: Relevance
“…The most common traumatic injuries identified on past admissions were orthopedic injuries, closed-head trauma, and burns. Additionally, having past traumatic injury was significantly associated with eventual hospitalizations for physical abuse, which indicates that a portion of the children with past abuse-related injuries [12,13,18,35] and subsequent hospitalization for abuse were likely cases of missed abuse. This failure of our healthcare system to detect abuse and attempt prevention of further abuse reveals an area for improvement in definitive identification and management of children with abuse.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The most common traumatic injuries identified on past admissions were orthopedic injuries, closed-head trauma, and burns. Additionally, having past traumatic injury was significantly associated with eventual hospitalizations for physical abuse, which indicates that a portion of the children with past abuse-related injuries [12,13,18,35] and subsequent hospitalization for abuse were likely cases of missed abuse. This failure of our healthcare system to detect abuse and attempt prevention of further abuse reveals an area for improvement in definitive identification and management of children with abuse.…”
Section: Discussionmentioning
confidence: 99%
“…The NRD data are also extensively processed to ensure that readmissions are counted as accurately as possible. This is especially important for trauma studies that utilize population-level data since it is possible that admissions related to the index injury could be miscoded as a new injury [18,19]. The NRD also greatly reduces the likelihood of this type of miscoding by collapsing multiple records into one if they involve a transfer or same-day event such as discharge and admission between different hospitals [20].…”
Section: Methodsmentioning
confidence: 99%
“…1,2 Previously identified risk factors associated with violent trauma include unemployment, lack of medical insurance, minority race, drug or substance abuse, and low income. 3,9,11 Our study population represents an age group previously identified as high-risk for violence-related trauma and captured any assault-related injury to evaluate for mechanism of injury as a potential risk factor. Our findings demonstrated trauma recidivism and mortality due to a second trauma occurred most commonly in patients surviving a GSW as their initial injury, as compared with stab wounds, blunt assault, and nonviolent trauma.…”
Section: Discussionmentioning
confidence: 99%
“…[3][4][5]9 Past studies have been limited in their ability to accurately capture patients after discharge, as this cohort is often lost to follow-up or present to different hospitals and outpatient providers, which are not captured by databases reviewing inpatient and/or ED admission. 10,11 Furthermore, most fatal firearm injuries occur at the scene or before ED arrival, limiting the ability of surveillance databases to accurately capture mortality rates outside a medical facility.…”
Section: Introductionmentioning
confidence: 99%
“…The ED is an important implementation setting for prevention, in part because a large proportion of patients will experience a subsequent assault-related injury or premature death within a few years of a treated injury ( 6 , 7 ). For example, one study compared persons aged 14–24 years who sought treatment in the ED and reported substance use in the 6 months before the visit.…”
Section: Discussionmentioning
confidence: 99%